Sistema integrado de gestão - compatibilização da norma NBR ISO 9001/2008 com os requisitos de excelência segundo Fundação Nacional da Qualidade (FNQ). - Sant'anna, Luiz Carlos de Campos (2009)
The basic objective of the quality management systems either based on the requirements of the NBR ISO 9001:2008 norms of management, either based on the criteria that give support to the National Foundation of Quality (FNQ), is to improve the indexes of quality, productivity and trustworthiness of the products and services of the organizations, as well as promoting guarantees for the customer. Based on these facts this work has as objective: to propose an alignment of NBR ISO 9001/2008 requirements with the criteria of excellency of the National Foundation of Quality (FNQ) - Commitment with the excellency, in companies with the intention to develop a system of management looking toward organizations in incipient managemental stage. For this the criteria of excellency of the FNQ had been interpreted - Commitment with the excellency and the requirements of NBR ISO 9001:2008, observing the methodological practices, using the exploratory, descriptive and clarifying research. Therefore at a first moment a bibliographical revision was made, looking for to have subsidies for the descriptive studies, that it aims at to characterize the evolution of the management concepts until the current days of the companies as well as the scene where these companies are inserted. Later was analyzed the compatibility of the criteria of the FNQ and the requirements of NBR ISO 9001:2008, through bibliographical research and multicriteria study in what it refers to the intention of this work aiming to establish a relationship between these systems of management improving the administration of the organizations in clarifying form. It was observed that both the programs are accurate its proposals of implantation, however with some proper peculiarities, the requirements of norm NBR ISO 9001:2008, are focused basically in the control of the processes and the attendance of the requirements of product defined for the customer, already the criteria of the FNQ are directed toward the results and establish practices for philosophical and mannering actions. The union of the culture of the organizacional quality spread by the FNQ lined up with the requirements of the guarantee of the quality of norm NBR ISO 9001:2008 will be able to create a positioning favorable to the organization that to follow this way. The result of this integration will create organizations that in fact will provide products and services in the market with quality, reduced costs, improved processes and increase of yield.